2019
DOI: 10.1182/blood.2018893545
|View full text |Cite
|
Sign up to set email alerts
|

Oral idasanutlin in patients with polycythemia vera

Abstract: A limited number of drugs are available to treat patients with polycythemia vera (PV) and essential thrombocythemia (ET). We attempted to identify alternative agents that may target abnormalities within malignant hematopoietic stem (HSCs) and progenitor cells (HPCs). Previously, MDM2 protein levels were shown to be upregulated in PV/ET CD34+ cells, and exposure to a nutlin, an MDM2 antagonist, induced activation of the TP53 pathway and selective depletion of PV HPCs/HSCs. This anticlonal activity was mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 29 publications
0
48
1
Order By: Relevance
“…Idasanutlin was well tolerated without dose-limiting toxicities. Five subjects (41.7%) experienced grade 3 non-hematologic AEs and grade 1/2 nausea occurred in 10 (83%) patients [106]. Idasanutlin is currently evaluated in a phase II trial (NCT03287245).…”
Section: Idasanutlinmentioning
confidence: 99%
“…Idasanutlin was well tolerated without dose-limiting toxicities. Five subjects (41.7%) experienced grade 3 non-hematologic AEs and grade 1/2 nausea occurred in 10 (83%) patients [106]. Idasanutlin is currently evaluated in a phase II trial (NCT03287245).…”
Section: Idasanutlinmentioning
confidence: 99%
“…Although IFNα targets JAK2 V617F hematopoietic progenitors, in patient or mouse models its long-term efficacy remains modest ( Austin et al, 2020 ; Gisslinger et al, 2020 ; Hasan et al, 2013 ; Kiladjian et al, 2006 ; Mullally et al, 2012 ). Several clinical and preclinical studies have attempted to improve IFNα efficacy, for example, through combinations with MDM2 or JAK2 inhibitors ( Austin et al, 2020 ; Lu et al, 2014 ; Mascarenhas et al, 2019 ). We demonstrate that the IFNα+ATO combination specifically targets the Jak2 V617F disease-initiating cells in vivo, with a much higher potency than IFNα alone.…”
Section: Resultsmentioning
confidence: 99%
“…These non-genotoxic compounds bind to MDM2 in the p53-binding pocket and can release p53, leading to effective stabilization of the protein and activation of the Tp53 pathway (Figure 4) [82,83]. Initial preclinical and clinical studies have demonstrated promising efficacy of this class of drugs in a number of TP53 wild type adult and pediatric cancers, both as single agents and in combination with other targeted therapies [84][85][86][87][88][89][90].…”
Section: Targeted Therapies That Potentiate P53 Functionmentioning
confidence: 99%